Adsorption of sulfur mustard on clean and water-saturated ZnO(101¯0): Structural diversity from first-principles calculations - Klöffel, Tobias; Kozlowska, Mariana; Popiel, Stanislaw; Meyer, Bernd; Rodziewicz, Pawel (Journal of Hazardous Materials, 2021)
We investigate the adsorption of a chemical warfare agent, namely sulfur mustard (SM), on clean and water-saturated ZnO(101¯0) surfaces using density functional theory calculations to understand the first step of its efficient neutralization to less toxic chemical compounds. We determine the relative stability of various SM conformers adsorbed at different sites on both ZnO surfaces. The unique hydrogen bonding patterns obtained for the idealized clean and the more realistic water-saturated ZnO surface are analyzed and their influence on the stability of the SM@ZnO structures is demonstrated. We find that absolute values of the calculated binding and interaction energies are significantly higher for the clean than for the water-saturated ZnO surface due to the formation of Cl⋯Zn and S⋯Zn contacts. The high adsorptive reactivity of the clean ZnO surface is also evident from the strong structural changes of the initial local energy minimum gas-phase conformations of the SM molecules upon adsorption. This phenomenon is not observed for the water-saturated ZnO surface, which has almost no impact on the SM conformation after adsorption, leaving it as it exists in the gas phase. The insights from the results obtained provide a missing piece toward the understanding of the complex mechanism of SM neutralization on ZnO surfaces.
CRIS-Team Scopus Importer:2020-08-07
Keywords: Bis(2-chloroethyl) sulfide; Chemical warfare agents; Density functional theory; Sulfur mustard; Zinc oxide